The Effect of Video and Advertorial Advertising Forms on Interest in Information Seeking - Monica Apilia; Bestian Nainggolan (The Journal of Society and Media, 2021)
There's very tough competition in today's business. Supported by a pandemic like what happened today, new Usaha Mikro Kecil Menengah (UMKMs) are increasingly emerging and producing products similar to products made by UMKMs that have started their business first. This situation impacts these UMKMs, where each UMKM must choose the right marketing strategy to increase consumer interest to search for information on products they sell. One of the things that they can do is to do marketing through social media, such as Instagram, which can be in advertisements in the form of videos or advertorials. Proper marketing can increase the interest in seeking information on the product they sell. The concept of AIDA (Attention, Interest, Desire, Action), especially in the dimensions of attention and interest, is used in this study. The purpose of this study is to see the effect of video and advertorial advertising forms on interest in information seeking. This research uses quantitative research methods with the type of experiment with the number of respondents as many as 124 people, where 60 people received treatment in the form of advertising in the form of video and 64 other people received treatment in the form of advertising with advertorial form. The results of this study indicate that the form of video ads and advertorials influences information-seeking interest. Video ads have a more significant effect on information-seeking interest than ads with advertorial forms.